NEGOTIATION OF MEANING IN COMMUNICATIVE TASKS - Luciana Thio (Indonesian JELT, 2005)
The adoption of task-based teaching in Indonesia classrooms has not been widely accepted for two major grounds. First, teachers seem to cast some doubts as to what degree such an approach can contribute to their students’ language development. Second, classroom management issues, such as discipline and noise become another challenge to cope with. While these issues deserve serious attention, teachers’ unwillingness to venture the use of tasks seems to put their awareness of the learning process at stake. It is through task-based teaching, students’ language development can be nurtured. This study is an attempt to probe the benefits of using two types of communicative tasks: picture comparison and picture drawing. The study involving two female Taiwanese native speakers learning English found that the interactional mechanisms created through a task and, negotiation of meaning provided a potentially rich forum for students’ language development. There are at least two prime elements accounting for this benefit. First, the type of direct indicators employed by the student creates linguistic urgency fostering the limit of their language capacity, and the use of embedded negotiation of meaning promotes students’ active involvement. Second, one way communicative tasks, to some degree, can yield greater opportunities for students to negotiate, thus enriching acquisition. Keywords: negotiation of meaning, communicative tasks.